Parallel Sequence Spread Spectrum-Orthogonal Frequency Division Multiplexing (PSSS-OFDM) scheme - a novel physical layer for robust wireless communication systems - Urriza, Paulo Isagani M. (2009)
Multi-carrier spread spectrum (MCSS) methods based on OFDM use a linear transform to spread energy of transmitted symbols over statistically independent Rayleigh fading subcarriers, in order to obtain diversity gain at the receiver. In this thesis, we present and investigate a novel MCSS system which uses Parallel Sequence Spread Spectrum (PSSS) as its spreading transform. This technique called PSSS-OFDM, allows flexible control over the amount of spreading to provide a variable rate link at minimal complexity gain over standard OFDM, requiring only a simple correlator before the IFFT block. Using a single-tap phase correction equalizer, simulations show a gain of 4dB in Eb/N0 at a BER of 0.1 over plain PSSS. With the additional complexity due to the FFT block and the equalizer, it is able to achieve data rates which are 9 to 10 times higher than PSSS giving it potential for use in wideband applications such as WLANs. Simulations show that PSSS-OFDM provides diversity gain over standard BPSK-OFDM by trading robustness for lower spectral efficiency. PSSS-OFDM achieves comparable BER to standard OFDM at approximately 50% of the spectral efficiency through the use of precoding. The scheme also performs progressively better againts OFDM as RMS delay spread is increased. Thus, PSSS-OFDM could be used to provide OFDM with multipath robustness in channels with high delay spread as a substitute for coded OFDM. Finally, to assess the feasibility of implementing PSSS-OFDM in hardware, the transceiver was developed and implemented in a Xilinx Virtex 4 XC4VFX12 platform through a rapid prototyping approach using Xilinx System Generator.
"August 2009."
Thesis (M.S. Electrical Engineering) -- University of the Philippines Diliman.
Keywords: Orthogonal frequency division multiplexing; Spread spectrum communications; Signal processing; Parallel sequence spread spectrum; Multi-carrier spread spectrum